Biomechanics and structural adaptations of the rat femur after hindlimb suspension and treadmill running - Shimano,M.M. (2009)
We microscopically and mechanically evaluated the femurs of rats subjected to hindlimb unloading (tail suspension) followed by treadmill training. Female Wistar rats were randomly divided into five groups containing 12-14 rats: control I (118 days old), control II (139 days old), suspended (tail suspension for 28 days), suspended-released (released for 21 days after 28 days of suspension), and suspended-trained (trained for 21 days after 28 days of suspension). We measured bone resistance by bending-compression mechanical tests of the entire proximal half of the femur and three-point bending tests of diaphyseal cortical bone. We determined bone microstructure by tetracycline labeling of trabecular and cortical bone. We found that tail suspension weakened bone (ultimate load = 86.3 ± 13.5 N, tenacity modulus = 0.027 ± 0.011 MPa·m vs ultimate load = 101.5 ± 10.5 N, tenacity modulus = 0.019 ± 0.006 MPa·m in control I animals). The tenacity modulus for suspended and released animals was 0.023 ± 0.010 MPa·m vs 0.046 ± 0.018 MPa·m for trained animals and 0.035 ± 0.010 MPa·m for control animals. These data indicate that normal activity and training resulted in recovered bone resistance, but suspended-released rats presented femoral head flattening and earlier closure of the growth plate. Microscopically, we found that suspension inhibited new bone subperiosteal and endosteal formation. The bone disuse atrophy secondary to hypoactivity in rats can be reversed by an early regime of exercising, which is more advantageous than ordinary cage activities alone.